The Influence of Understanding the Accountant Professional Code of Ethics, Love of Money, Religiosity, and Equity Sensitivity (E-Jurnal Akuntansi, 2025)
The aim of this study was to determine the effect of understanding the accounting profession's code of ethics, love of money, religiosity and equity sensitivity on accounting students' ethical perceptions. The population in this study were all Bachelor of Accounting Study Program batch 2019 students at the Faculty of Economics and Business, Udayana University. The research sample was 255 people using the purposive sampling method. The data analysis technique used in this study is multiple linear regression. Research shows that understanding the ethical code of the accounting profession, Love of Money, religiosity, and Equity Sensitivity have a positive effect on ethical perceptions of accounting students. The implication of this research is that Udayana University, especially the Faculty of Economics and Business, undergraduate accounting study program can evaluate the understanding of the accounting profession's code of ethics, Love of Money, religiosity and Equity Sensitivity because this can influence the ethical perceptions of accounting students so that students have high ethical perceptions and ready to enter the world of work to become a professional accountant in the future.
Keywords: Accountant Professional Code of Ethics; Love of Money; Religiosity; Equity Sensitivity and Ethical Perceptions